Implementation and evaluation of a weight-reduction programme for diabetic patients at a primary health care facility in the Western Cape: a pilot study. Issue 6 (2nd November 2017) - Razak, A; Isaacs, AA
Abstract : Background: Diabetes is a common non-communicable disease and complications are resulting in increased disability, reduced life expectancy and enormous health costs for virtually every society. Medical Nutrition Therapy is important for the prevention, treatment, and self-management of diabetes, and the prevention or delay in onset of diabetes-related complications. The current nutritional guidelines for diabetes state that carbohydrates should comprise 45–60% of the total nutritional intake and that low-carbohydrate or high-protein diets offer no long-term success over healthy eating plans. Recent studies suggest that there may be merit in using low-carbohydrate diets in diabetic patients for weight reduction and improved cardiovascular markers. This study aimed to implement and evaluate a pilot programme for weight loss in diabetes mellitus type 2 patients by comparing a low-carbohydrate diet with the conventional low-fat diet. Methods: The study design was that of a two-group parallel design, with one group following a low-fat diet and the other a low-carbohydrate diet. Diabetic patients attending the Mitchell's Plain Community Health Centre in Cape Town were recruited, with 10 participants in each group. Both groups received similar advice on exercise and behaviour change. Changes in weight, waist circumference, blood pressure and blood parameters (creatinine, lipids and HbA1c) were recorded at baseline and again after 12 weeks. Results: There were reductions in weight (1.85 kg vs. 0.1 kg gain) and HbA1c (1.72 vs. 0.32) in the low-carbohydrate diet group when compared with the low-fat diet group. No significant change was seen in other parameters including BP, total cholesterol and serum creatinine for either group. Conclusion: Low-carbohydrate diets may be effective in promoting weight loss and improving glucose control in diabetic patients. Implementation of this programme would require a paradigm shift for staff and further studies to assess its acceptability for patients.